2008
DOI: 10.1021/la803235x
|View full text |Cite
|
Sign up to set email alerts
|

Driving Force Behind Adsorption-Induced Protein Unfolding: A Time-Resolved X-ray Reflectivity Study on Lysozyme Adsorbed at an Air/Water Interface

Abstract: Time-resolved X-ray reflectivity measurements for lysozyme (LSZ) adsorbed at an air/water interface were performed to study the mechanism of adsorption-induced protein unfolding. The time dependence of the density profile at the air/water interface revealed that the molecular conformation changed significantly during adsorption. Taking into account previous work using Fourier transform infrared (FTIR) spectroscopy, we propose that the LSZ molecules initially adsorbed on the air/water interface have a flat unfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
79
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 18 publications
5
79
2
Order By: Relevance
“…23 We found that the LSZ molecule initially adsorbed by adopting a flat, unfolded structure as a result of hydrophobic interactions with the gas phase. In contrast, as adsorption continues, the LSZ molecules gradually adapt their configuration to the surroundings.…”
Section: Section: Macromolecules Soft Mattermentioning
confidence: 86%
“…23 We found that the LSZ molecule initially adsorbed by adopting a flat, unfolded structure as a result of hydrophobic interactions with the gas phase. In contrast, as adsorption continues, the LSZ molecules gradually adapt their configuration to the surroundings.…”
Section: Section: Macromolecules Soft Mattermentioning
confidence: 86%
“…These differences can be explained by the stronger effect of the interface on the structure of lysozyme compared to BSA and BLG. In [7], it was revealed that the second ary structure of lysozyme changes more markedly dur ing the adsorption than do the structures of the two lat ter proteins. Seemingly, when lysozyme complexes with several SDS molecules are adsorbed in the region of specific binding, the tertiary structure is also some what changed and the adsorption film becomes looser.…”
Section: Resultsmentioning
confidence: 99%
“…The degree of the breakage of the globular structure of proteins upon their adsorption on a liquid surface is still intensely discussed [1][2][3][4][5][6][7][8][9][10][11]. Although the main stages of many processes in living organisms occur at interfaces and protein adsorption layers stabilize vari ous natural and industrial disperse systems, informa tion on variations in the tertiary and secondary struc tures of proteins during adsorption is extremely scarce.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations